#### Answer

$r'(x) = (4-x)^{-\frac{3}{2}}$
So,
$r'(0) = \frac{1}{8}$

#### Work Step by Step

$r(x) = \frac{2}{\sqrt (4-x)}$
$r'(x) = 2(-\frac{1}{2})(4-x)^{-\frac{3}{2}}(-1)$
$r'(x) = (4-x)^{-\frac{3}{2}}$
So,
$r'(0) = \frac{1}{8}$

Published by
Pearson

ISBN 10:
0321999584

ISBN 13:
978-0-32199-958-0

$r'(x) = (4-x)^{-\frac{3}{2}}$
So,
$r'(0) = \frac{1}{8}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.